The Influence of Financial Self-Efficacy and Financial Well-Being on Gen-Z in Padang City: The Role of Financial Behavior as a Mediator - Putra Pernando; Abel Tasman (CV. Muris Global Education, 2026)
This study aims to analyze the effect of financial self-efficacy on financial well-being with financial behavior as a mediating variable in Generation Z who have worked in Padang City. This study is motivated by the still low level of financial well-being of Generation Z, which is influenced by low confidence in managing finances and suboptimal financial behavior. The study used a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research sample consisted of 200 respondents selected using a purposive sampling technique. The results showed that financial self-efficacy had a positive and significant effect on financial behavior and financial well-being. In addition, financial behavior also had a positive and significant effect on financial well-being. The results of the mediation test proved that financial behavior was able to positively and significantly mediate the effect of financial self-efficacy on financial well-being. These findings indicate that improving the financial well-being of Generation Z is not only influenced by individual confidence in managing finances but also by the ability to apply good financial behavior in everyday life.